2022
DOI: 10.3389/fendo.2022.890273
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Globulin and Diabetic Nephropathy in Type2 Diabetes Mellitus Patients: A Cross-Sectional Study

Abstract: BackgroundWith the development of economy, the living standard of people all over the world has been greatly improved, and the incidence of diabetes is also increasing. Many people with diabetes also develop other complications that reduce their quality of life. Diabetic nephropathy is a common complication of type2 diabetes. Understanding the related factors of diabetic nephropathy is greatly significant to control the occurrence of diabetic nephropathy and improve patient’s life quality.Data and MethodsData … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
0
23
1
Order By: Relevance
“…The results of the current study are parallel with those of cross-sectional studies. [15,17,23] A cross-sectional study [15] was performed on the Chinese population on the NHANES official website, but inclusion criteria were limited. A cross-sectional study performed on the Egyptian population [17] had a small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the current study are parallel with those of cross-sectional studies. [15,17,23] A cross-sectional study [15] was performed on the Chinese population on the NHANES official website, but inclusion criteria were limited. A cross-sectional study performed on the Egyptian population [17] had a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…From 18.5 to 24.9 kg/m 2 was considered a normal BMI, from 25 to 29.9 kg/m 2 was considered overweight, and 30 kg/m 2 or more was considered obese. [15]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the authors adjusted more biochemical parameters in the present study, including ALB, GLB, DBIL, and BUN. Evidence showed that those parameters were associated with Pre-DM [29][30][31][32]. In testing the robustness of the results by a set of sensitivity analyses (target independent variable transformation, subgroup analysis and using a GAM to insert the continuity covariate into the equation as a curve), the stronger positive association was found in female and the population with 30 years < age < 40 years, 18.5 kg/m 2 ≤ BMI < 24 kg/ m 2 , and ALT ≤ 40U/L, which would be the spotlight of attention in clinic.…”
Section: Discussionmentioning
confidence: 99%